Analysis of the Effect of Social Media on Formation of Brand Awareness and Brand Image for Customers CitraLand Surabaya - Parastati, Nada Putri (Universitas Ciputra Surabaya, 2022)
This study aims to determine the influence of social media on Brand Awareness and BrandImage of CitraLand Surabaya real estate, so as to increase sales of CitraLand Surabaya products and thenumber of potential customers. The variables studied were the social media variable (X) as the independentvariable, the Brand Awareness variable (Y1) as the intervening variable, and the Brand Image variable(Y2) as the dependent variable. The analysis method used is descriptive statistical analysis and pathanalysis. The population of this research is the residents of CitraLand Surabaya real estate. The survey wasconducted on 102 respondents. Path analysis result showed that social media had a positive and significanteffect, and had a greater influence on Brand Image directly than indirectly or through Brand Awareness asan intervening variable. The study results showed that social media has a positive and significant impact onBrand Awareness and Brand Image, while Brand Awareness also has a positive and significant impact onBrand Image.